Pembatalan Sertifikat Pelatihan Peningkatan Kualitas Jabatan Notaris Sebagai Syarat Pengangkatan Notaris (Studi Putusan Mahkamah Agung Nomor3P/HUM/2022) - Indah Delima Fitrah; Busyra Azheri; Wetria Fauzi (LPPM Universitas Ekasakti Padang, 2023)
Through Supreme Court Decision Number 3 P/HUM/2022, the request for judicial review of Article 2 paragraph (3) letter of Minister of Law and Human Rights Regulation Number 19 of 2019 was granted, which implied canceling one of the conditions for appointing a Notary, namely a photocopy of the Quality Improvement Training certificate Notary Position. The research method used is normative juridical, with a case approach. The results of the author's findings are that the Supreme Court thinks that legal norms which have been tested and declared to conflict with higher laws and regulations and declared to have no binding legal force, may not be re-published in a regulation. After the Supreme Court Decision Number 3 P/HUM/2022, the process of appointing Notaries in 2022 still uses reference to Article 2 of the Regulation of the Minister of Law and Human Rights Number 19 of 2019 as a whole, including Training to Improve the Quality of Notary Positions as a condition for appointing Notaries. So, prospective Notaries who have completed all the requirements other than Training to Improve the Quality of Notary Positions, cannot apply for appointment.